2015
DOI: 10.1037/lhb0000122
|View full text |Cite
|
Sign up to set email alerts
|

The (ir)relevance of procedural justice in the pathways to crime.

Abstract: Process-based approaches to compliance argue that normative considerations, such as procedural justice and legitimacy, have the potential to reduce offending. This perspective was formalized with Tyler's (1990, 2003) Model of Procedural Justice and subsequently was evaluated among adult and adolescent offenders alike. However, extant evaluations do not consider whether and how individual offending histories affect the relevance of the concepts of procedural justice and legitimacy on offending behavior. This vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 68 publications
1
34
0
1
Order By: Relevance
“…However, the most striking of our findings was that an interaction between personal experiences of corruption and perceptions of police fairness increased the likelihood of self-reported law-breaking on the roads among the drivers surveyed. To our knowledge, Augustyn's (2015) study in the United States is the only correlational study to have reported counterintuitive results involving perceived police fairness: she analysed data from 1,354 adolescent offenders and found that judgments of procedural justice increased the frequency of offending among adolescent-onset offenders (p. 394). Augustyn (2015) conjectured that: Perhaps […] positive evaluations of procedural justice with the police and courts indicate a lack of trepidation or fear of subsequent interactions with legal authorities.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most striking of our findings was that an interaction between personal experiences of corruption and perceptions of police fairness increased the likelihood of self-reported law-breaking on the roads among the drivers surveyed. To our knowledge, Augustyn's (2015) study in the United States is the only correlational study to have reported counterintuitive results involving perceived police fairness: she analysed data from 1,354 adolescent offenders and found that judgments of procedural justice increased the frequency of offending among adolescent-onset offenders (p. 394). Augustyn (2015) conjectured that: Perhaps […] positive evaluations of procedural justice with the police and courts indicate a lack of trepidation or fear of subsequent interactions with legal authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that justice system attitudes have direct consequences for crime commission during both adolescence and adulthood [1,10,24,43,60], it is essential to understand whether justice system attitudes remain stable from adolescence through early adulthood. Further, considering the salience of race/ethnicity to justice system exposure, it is likely that legal socialization experiences vary by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the results confirm that judgments of procedural justice are not static; rather, they are malleable as are many other attitudes and perceptions during adolescence and young adulthood. Even among this group of serious adolescent offenders with largely negative views regarding the criminal justice system and an increased proclivity to engage in crime (Mulvey 2004), judgments of procedural justice can and do change and if this change is positive, then compliance with the law is more likely (Augustyn 2015; Fagan and Piquero 2007; Penner et al 2014).…”
Section: Discussionmentioning
confidence: 99%